Review: Lasmiditan Drug Discovery for Acute Migraine Treatment - Savira, Amelia; Mustika, Meilinda; Asra, Ridho (Asian Journal of Pharmaceutical Research and Development, 2021)
Background: Lasmiditan is a compound developed by Eli Lilly and Company named REYVOW®. Lasmiditan is a highly selective 5-hydroxytryptamine (5-HT1F) receptor agonist, indicated for the treatment of acute migraine with or without aura. Objective: This review article aimed to discuss the review of the drug discovery of lasmiditan. Data Source: The author made this review article using the literature study method that is relevant to the purpose of the review. Sources of information from national journals and international journals are accessed through online sites such as Google Scholar, Research Gate, Science Direct, Springer Link, and NCBI. The keywords used to search for journals are Lasmiditan, Migraine, Reyvow®. Conclusion: Lasmiditan is a highly selective 5-hydroxytryptamine (5-HT1F) receptor agonist, lasmiditan is the only drug approved for the treatment of acute migraine with or without aura whose mechanism of action is specific to the 5-HT1F receptor which has no vasoconstrictive effect.